Genetic diversity and population structure in the Ryukyu flying fox inferred from remote sampling in the Yaeyama archipelago. - Yuto Taki; Christian E Vincenot; Yu Sato; Miho Inoue-Murayama (PLoS ONE, 2021)
The Ryukyu flying fox (Pteropus dasymallus) is distributed throughout the island chain spanning across southern Japan, Taiwan, and possibly the Philippines. Although P. dasymallus is listed as VU (vulnerable) in the IUCN Red List, only few genetic works have been conducted to support its conservation. In this study we analyzed 19 markers (mtDNA haplotypes and 18 microsatellite markers) to evaluate genetic diversity and investigate the genetic structure of this species. mtDNA analysis was conducted with 142 DNA remote samples, mostly from faeces, and wing tissues collected on eight islands (Miyako, Ishigaki, Kohama, Kuroshima, Hateruma, Taketomi, Iriomote, Yonaguni). 39 haplotypes were identified in 526bp of the control region, and haplotype network showed no clear genetic structure. Microsatellite analysis was also conducted with 155 samples collected on six islands (Miyako, Ishigaki, Kohama, Taketomi, Iriomote, Yonaguni). It showed that the Yonaguni population exhibits low genetic diversity, high inbreeding, and clear genetic differentiation from other populations. Gene flow between Ishigaki and Miyako through small stepstone islands might be preventing inbreeding of the Miyako population. We provide for the first time indirect proof of long-distance inter-island dispersal in the Ryukyu flying fox and revealed genetic diversity, gene flow and genetic differentiation among the archipelago's populations. These results will be useful for delineating conservation units and designing specific conservation policies for each island based on metapopulation genetic structure.